Canadian Thoracic Society Recommendations for Management of Chronic Obstructive Pulmonary Disease – 2008 Update – Highlights for Primary Care. (2008) - O'Donnell, Denis E; Hernandez, Paul; Kaplan, Alan; Aaron, Shawn; Bourbeau, Jean; Marciniuk, Darcy; Balter, Meyer; Ford, Gordon; Gervais, Andre; Lacasse, Yves; Maltais, Francois; Road, Jeremy; et al.
Abstract : Chronic obstructive pulmonary disease (COPD) is a major respiratory illness in Canada that is preventable and treatable but unfortunately remains underdiagnosed. The purpose of the present article from the Canadian Thoracic Society is to provide up-to-date information so that patients with this condition receive optimal care that is firmly based on scientific evidence. Important summary messages for clinicians are derived from the more detailed Update publication and are highlighted throughout the document. Three key messages contained in the update are: use targeted screening spirometry to establish a diagnosis and initiate prompt management (including smoking cessation) of mild COPD; improve dyspnea and activity limitation in stable COPD using new evidence-based treatment algorithms; and understand the importance of preventing and managing acute exacerbations, particularly in moderate to severe disease.